Insights into spelling mistakes experiences by UAE students - Hassan, Azzam Halamo Abdullah (2010)
Purpose – This paper aims to study the particular difficulties experienced by UAE grade 12 students in learning English spelling. The purpose is to examine the students’ written work in CEPA (Common Educational Proficiency Assessment ) Exam files to identify the most frequent and common spelling mistakes that UAE students encounter as they learn to spell in English, a language that is very different from students’ L1 (Arabic) both morphologically and orthographically. Methodology – Two major procedures were employed to achieve the purpose of the study. The first procedure was the use of modern technology (Antconc software) to trace the spelling mistakes found in the BALC (BUiD Arab Learner Corpus). Then, the most frequent mistakes were extracted from the Corpus, classified under different categories; and then the most frequent common ones were indentified. The next procedure was distributing a questionnaire to a number of grade 12 English Language teachers to share their perspectives about spelling difficulties in general and to find out possible solutions that can be used to eradicate spelling problems and help to enhance students’ ability in mastering the English spelling skill. Findings – The study revealed that UAE grade 12 students experienced frequent common spelling problems particularly in general vowel orthography (mainly short and long vowel words), deleting final e, syllable junctures, syllable rimes, and consonant doubling. The study also came up with the fact that one of the main reasons beyond these mistakes is that students were highly influenced by their L1 orthography. The value – The awareness of the revealed frequent common mistakes is of great significance to teachers of English, educators as well as to researchers. Upon the findings of this study, appropriate methods can be applied to tackle spelling problematic areas. It is hoped that the recommendations and results of this study could be of much benefit for developing the skill of teaching and learning English spelling in the UAE schools.